2016
DOI: 10.1021/acs.jmedchem.5b02025
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a 9-mer Cationic Peptide (LTX-315) as a Potential First in Class Oncolytic Peptide

Abstract: Oncolytic immunotherapies represent a new promising strategy in the treatment of cancer. In our efforts to develop oncolytic peptides, we identified a series of chemically modified 9-mer cationic peptides that were highly effective against both drug-resistant and drug-sensitive cancer cells and with lower toxicity toward normal cells. Among these peptides, LTX-315 displayed superior anticancer activity and was selected as a lead candidate. This peptide showed relative high plasma protein binding abilities and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
81
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(84 citation statements)
references
References 56 publications
(77 reference statements)
3
81
0
Order By: Relevance
“…Comparisons of Kaplan-Meier survival curves were performed using the log-rank Mantel-Cox test; NS, not significant LTX-315 overcomes anti-CTLA4 resistance T Yamazaki et al manner by inducing cell death endowed with immunogenic properties. [25][26][27][28][29][30][31][32][33][34][35] In this preclinical study, we found that LTX-315 can be active against sarcomas that poorly respond to CTLA4 blockade, and that the sequential combination of anti-CTLA4 mAb followed by LTX-315 is synergistic, either using systemic or local delivery of anti-CTLA4 mAb, with a mechanism involving CD122 receptors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparisons of Kaplan-Meier survival curves were performed using the log-rank Mantel-Cox test; NS, not significant LTX-315 overcomes anti-CTLA4 resistance T Yamazaki et al manner by inducing cell death endowed with immunogenic properties. [25][26][27][28][29][30][31][32][33][34][35] In this preclinical study, we found that LTX-315 can be active against sarcomas that poorly respond to CTLA4 blockade, and that the sequential combination of anti-CTLA4 mAb followed by LTX-315 is synergistic, either using systemic or local delivery of anti-CTLA4 mAb, with a mechanism involving CD122 receptors.…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21][22][23][24] The chemical modifications of bovine lactoferricin derivatives allowed for the development of a lead compound, LTX-315 with a shorter chemically modified peptide length and optimal (selective) anticancer properties. [25][26][27][28][29] By creating pores and disintegrating the cytoplasmic membranes, as well as targeting the mitochondria, LTX-315 promotes the release of damage-associated molecular patterns (DAMPs) associated with immunogenic cell death (ICD). 26,27,29 Transmission electron microscopy or morphometric analysis of chromatin-stained tumor cells revealed that LTX-315 failed to induce classical 'apoptosis' associated with apoptotic nuclear condensation and caspase-3-dependent cell death.…”
mentioning
confidence: 99%
“…The design of this new peptide was originally derived from LFcinB and was the result of extensive structure-activity relationship studies (Haug et al 2016). In terms of hLF, the peptide derived from the first 11 residues (hLF11) has been extensively studied for its antimicrobial activity against several bacterial and fungal strains (Lupetti et al 2000, Nibbering et al 2001.…”
Section: R a F Tmentioning
confidence: 99%
“…The vast amount of SAR-data on lactoferricinderived, and also synthetic model peptides has facilitated the de novo design of 9-mer cationic peptides in which counterproductive residues have been deleted and the properties of residues identified as important for anticancer activity have been optimized, thereby resulting in a series of 9-mers composed of five cationic residues, two or three tryptophan residues and one or two bulky and lipophilic unnatural residues [29]. These peptides were found to be highly effective against both drug-resistant and drug-sensitive cancer cells, and displayed a lower activity toward normal cells.…”
mentioning
confidence: 99%
“…LTX-315 has been shown to be highly active against a wide variety of both murine and human cancer cell lines in vitro [29][30][31][32][33][34].…”
mentioning
confidence: 99%